Strategi Advokasi Kesehatan untuk Percepatan Penurunan Stunting: Studi Literatur Review - Miftahurrahmah El Hayatli; Annisa Annisa; Nabila Fitri; Nur Atikah Sari Br Rambe; Naufal Allamsyah (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Stunting is a public health issue in Indonesia that requires comprehensive intervention through the involvement of various stakeholders. Health advocacy plays a crucial role in building policy commitment, strengthening cross-sectoral coordination, and increasing community participation in accelerating the reduction of stunting. This study aims to identify and analyze various health advocacy strategies implemented to accelerate the reduction of stunting. The study employed a literature review method with a descriptive approach. Data sources were obtained from relevant national journals through a search on the Google Scholar database using the keywords “health advocacy” and “stunting reduction strategies.” Literature selection was based on inclusion criteria, namely scientific articles discussing advocacy strategies or efforts to reduce stunting, published between 2020 and 2025, and available in full text. The exclusion criteria included articles that were irrelevant to the topic, incomplete, or lacked clear sources and data. The results of the review of the ten articles indicate that the most commonly implemented advocacy strategies include advocating with the government to secure policy and budgetary support, strengthening cross-sectoral coordination, empowering communities through community health workers and integrated health posts (posyandu), nutrition education, utilizing communication media, and interventions during the first 1,000 Days of Life (HPK). These strategies have been shown to support increased stakeholder commitment and the effectiveness of stunting prevention programs. Thus, integrated, sustainable, and evidence-based health advocacy is a critical factor in accelerating the reduction of stunting in Indonesia.